Make your money count - Torabi, Farnoosh (FT Press Delivers elements., 2011)
"This Element is an excerpt from Psych yourself rich: Get the mindset and discipline you need to build your financial life (ISBN: 9780137079278) by Farnoosh Torabi. How to determine what's worth spending money on, and what isn't (hint: your best investment is yourself!)."--Resource description page.